The application of Hackman and Oldham’s job characteristics model to job satisfaction: view point from fast food outlet’ managers / Syukrina Alini Mat Ali , Noor Azzah Said and Rudzi Munap - Mat Ali, Syukrina Alini; Said, Noor Azzah; Munap, Rudzi (Research Management Institute (RMI), 2012)
This study examined to give the picture about the application of Hackman and Oldham’s job characteristics model to job satisfaction from the viewpoint of fast food outlet managers. The main objective of this study is to determine the relationship between job characteristics and job satisfaction among managers at fast food outlets and to determine which of the five dimensions of the job characteristics model contribute most to job satisfaction among fast food outlet managers. For this research, the population of 212 respondents who are from the managerial level from fast food outlet involved was being surveyed. 122 questionnaires were distributed to all the respondents. The five likert-scales were used to the statements based on job characteristics and job satisfaction. The researcher asked the respondents to rate the series of statement that evolve from their viewpoints of job characteristics and job satisfaction. Meanwhile the factors that contribute to job characteristics are autonomy, feedback, skill variety, task identity and task significance. The five main factors may become the strong or weakness factors that contribute to the relationship between job characteristics and job satisfaction. Then, the strongest relationship may be as the primary factor that should consider in ensuring the job satisfaction among manager at fast food outlet.